Boosting Electroreduction of CO2 to Tunable Syngas by Using a Pd‐Based Trimetallic Alloy. Issue 2 (29th November 2022) - Yang, Shuai; Zhan, Peng; Si, Zhihao; Li, Guozhen; Chu, Mengen; Liu, Chang; Lu, Lu; Qin, Peiyong
Abstract: Electrochemical reduction of CO2 to produce syngas is an ideal way to alleviate energy crisis and excessive CO2 emissions. The doping of additional elements to the Pd‐based material to form alloy is expected to result in catalyst with high activity, wide CO/H2 ratio and excellent stability for production on different platform chemicals. Here, Cu and Co species in the trimetallic alloy are targeted to solve the problems of Pd, the electronic structure and the synergistic interaction of alloy have a major effect on the reaction pathway. The obtained PdCuCo can achieve high Faradaic efficiency of CO (87.5% at −1.16 V vs RHE) and has a wide range of tunable CO/H2 ratio (from 0.44 to 7). In different downstream application scenarios, PdCuCo can provide high current densities for syngas preparation (44.4 mA cm −2 for Fischer‐Tropsch synthesis, 54.1 mA cm −2 for aldehyde production and 75.8 mA cm −2 for methanol production). Abstract : A trimetallic alloy PdCuCo constructed by introducing Cu and Co components to modify Pd‐based nanoparticles results in efficient electroreduction of CO2 to tunable syngas through synergistic effects and the modified electronic structure of the catalyst.